Pengaruh Harga dan Kualitas Produk Terhadap Keputusan Pembelian Pada Era Covid 19 (Studi Kasus di PT. Erje London Chemical) - Fidellis Wato Tholok; Suhendar Janamarta; Fx.Pudjo Wibowo (Komunitas Dosen Indonesia, 2021)
The purpose of this research is to determine the price and quality of the product partially (individually) or simultaneously (jointly) on Purchasing Decisions in the Covid Era (Case Study at PT. Erje London Chemical). The research was carried out by distributing questionnaires, moderate the research method using Simple Random Sampling. The independent variables in this study are Price and Product Quality, while the dependent variable in this study is the Purchasing Decision in the Covid 19 Era. Data collection methods are used by distributing questionnaires directly to consumers who buy products at PT. Erje London Chemical .. The analytical method used in this study uses the coefficient of determination analysis, multiple regression analysis of the F test and t test, using SPSS Version 25.00 which is based on data from 100 consumers who buy products at PT. Erje London Chemical .. The t test shows that the price variable (X1) partially has a positive and significant effect ((t value of price is 2.843.> T table 1.66071 and .005 <0.05 on Purchasing Decisions in the Covid 19 Era). PT Erje London Chemical) and product quality variables (X2) partially have a positive and significant effect (t value of product quality is 2.843> t table 1.66071 and .020 <0.05 on Purchasing Decisions in the Covid 19 Era (Case Study at PT Erje London Chemical ) and From the results of the F test, the results obtained for the calculated F value of 30,918 with a significance value of 0.000 so that the F value count> F table or 249.643> 3.09 or the significance level (sig) 0.000 <0.05, it can be concluded that it influences simultaneously (together -sama) between Price and Product Quality on Purchasing Decisions in the Covid 19 Era (Case Study at PT Erje London Chemical) and the adjusted R2 value in this study means that the variance in Purchase decisions in the Covid 19 Era (Case Study at PT Erje London Chemical) and can be explained by the price and product quality through a model of 56.3% and the remaining 43.7% comes from other variables outside of price and product quality variables. Or in other words, the amount of contribution / contribution of price and product quality is 56.3.9%, the remaining 43.7% comes from variables other than price and product quality variables.